Vitamin D Level in Children Is Correlated with Severity of Atopic Dermatitis but Only in Patients with Allergic Sensitizations. Issue 3 (7th January 2013) - Akan, Aysegul; Azkur, Dilek; Ginis, Tayfur; Toyran, Muge; Kaya, Aysenur; Vezir, Emine; Özcan, Celal; Ginis, Zeynep; Kocabas, Can Naci
Abstract: Vitamin D is believed to affect the progression and severity of atopic dermatitis (AD). Allergic sensitization may cause this effect to vary. Individuals who fulfilled the Hanifin and Rajka criteria for AD underwent epidermal prick tests and blood tests for specific immunoglobulin E(IgE), serum total IgE, 25‐hydroxy vitamin D, and peripheral blood eosinophil count and percentage. Disease severity was determined according to the Scoring Atopic Dermatitis (SCORAD) index. Patients were grouped according to allergic sensitization. Seventy‐three children with AD (median age 33.0 mos, interquartile range 19.0–61.5 mos) were enrolled in the study; 33 (45.2%) were found to have allergic sensitization. In this group there was a negative correlation between SCORAD score and serum vitamin D level (p = 0.047, correlation coefficient [r] = −0.349), whereas there was no correlation in the group without sensitization (p = 0.30, r = −0.168). Vitamin D was not correlated with total IgE and eosinophil percentage in either AD group (p = 0.77, r = 0.054 and p = 0.73, r = −0.062, respectively). Vitamin D may affect the severity of AD, especially in children with allergic sensitization.